(untitled) (Asian Journal of Plant Biology, 2015)
Glycine wightii species is an important perennial soybean. Tissue culture of in vitro cells, tissues and organs of Glycine wightii can yield efficient means in the genetics of breeding genetics, understanding the physiology and biochemistry of legumes. Most often than not, callus growth curve is sigmoidal in characteristics. In this work, we model callus growth from Glycine wightii from published literature to acquire essential growth constants. Previously, we model the growth of callus of Glycine wightii from published literature to obtain vital growth constants. We discovered that the modified Gompertz model via nonlinear regression utilizing the least square method was the best model to explain the growth curve. Nonlinear regression utilizing the least square method typically utilizes the idea that data points usually do not depend upon each other or the value of a data point is not determined by the value of previous or proceeding data points or usually do not display autocorrelation. In this work, the Durbin-Watson statistic to check for the presence of autocorrelation in the growth model was carried out, and showed that the modified Gompertz model was adequate to model the callus growth curve.